(untitled) (Biological Sciences - PJSIR, 2006)
Preventive methods were investigated against the Indian crested porcupine as it seriously damages trees, field crops, and vegetables. Large-scale field trials were conducted to determine the efficacy of two poison baits (0.0375% coumatetralyl and 2% zinc phosphide) and two fumigants (carbon monoxide and calcium cyanide powder) against the Indian crested porcupine, Hystrix indica, in forest plantations, ‘barani’ or drylands, and desert rangelands. On the average, carbon monoxide, calcium cyanide and coumatetralyl caused 95.84, 96.52, and 100% mortality, and were equally effective. The zinc phosphide bait yielded 27.78% mortality, indicating that it was less effective and poorly consumed by the porcupines. Use of the two fumigants and the grain bait of coumatetralyl was found to be excellent for the control of Indian crested porcupines in different habitats.